2011
DOI: 10.1021/jp200575u
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Adsorption of Ag Clusters on the Anatase TiO2(100) Surface

Abstract: The adsorption of silver atoms, dimers, tetramers, and octamers on the perfect anatase (100) surface has been studied theoretically at density functional theory level. Two complementary approaches based on linear combinations of atom-centered Gaussian-type basis functions and plane waves were applied. The most preferable adsorption positions were found to be hollow sites between two-coordinated oxygen atoms (O(2c)). Adsorption on the Ti–O planes is energetically less favorable. The binding mechanism was interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 66 publications
6
56
0
1
Order By: Relevance
“…In 2011, Mazheika et al found that the aggregation of Ag clusters on the (100) surface of anatase TiO 2 is an exothermic process with the use of GGA-PBE method combined with linear combinations of atom-centered Gaussian-type basis functions (LCAO), which results in the formation of three-dimensional clusters. [148] The favorable locations of adsorbed Ag clusters are the hollow sites between two-coordinated oxygen atoms. The adsorbed clusters are positively charged because of charge transfer to oxygen atoms or to unoccupied Ti orbitals.…”
Section: Ag/tio 2 and Ru/tiomentioning
confidence: 99%
“…In 2011, Mazheika et al found that the aggregation of Ag clusters on the (100) surface of anatase TiO 2 is an exothermic process with the use of GGA-PBE method combined with linear combinations of atom-centered Gaussian-type basis functions (LCAO), which results in the formation of three-dimensional clusters. [148] The favorable locations of adsorbed Ag clusters are the hollow sites between two-coordinated oxygen atoms. The adsorbed clusters are positively charged because of charge transfer to oxygen atoms or to unoccupied Ti orbitals.…”
Section: Ag/tio 2 and Ru/tiomentioning
confidence: 99%
“…73 Moreover, a three-dimensional configuration with tetrahedral shape was reported as the most stable isomer for Ag 4 on a-TiO 2 (100) 73 a-TiO 2 (101) 74 and r-TiO 2 (110) 70 surfaces. However, we have checked this structure and we found that it is unstable on a-TiO 2 (101).…”
Section: Adsorption On A-tio 2 No Vdw Interactionsmentioning
confidence: 99%
“…Several examples of these composites were presented recently, also including titania-based materials. [24][25][26][27] More specifically, titania can be combined with a metal, [28][29][30][31][32][33] graphene, [34,35] or another oxide. [19,20,36,37] Composites can be also created by interfacing two different polymorphs of TiO 2 , [38][39][40][41][42][43] or even two different faces of the same polymorph.…”
Section: Introductionmentioning
confidence: 99%